Caracterização psicológica de pacientes com reganho de peso pós-cirurgia bariátrica - Pereira, Janiele Francine (2017)
obesity is a multifactorial disease characterized by excessive body fat accumulation. Objectives: to describe sociodemographic profile of patients who underwent bariatric surgery more than 24 months ago, to investigate presence of symptoms and mental disorders and to assess the evolution of weight lost / gain after surgery. Method: the study was approved by FAMERP Ethics Committee. Patients who underwent bariatric surgery between July and December/2012 at Hospital de Base, São José do Rio Preto, SP, were invited to participate by filling a sociodemographic questionnaire, the Binge-Eating Scale (ECAP), the Hospital Anxiety and Depression Scale (HAD), the CAGE to assess the level of alcohol dependence screening test for problem drinking, the Sexual Addiction Screening Scale, and an analogic scale to assess patients´ satisfaction with surgery. Results: participants were 19 patients (mean age: 44.11 ± 8.90), predominantly females (n = 18), white, married, graduated from high school, working on the tertiary sector, with a family income of one and a half minimum wage, and from the Sao Jose do Rio Preto area. Eleven, of the 26 participants presented weight regain. Data from the questionnaires indicated binge eating 9,09% (n=1), anxiety symptoms 18,18% (n=2), depressive symptoms 18,18% (n=2), alcohol abuse 18,18% (n=2) and sex addiction 36,36% (n=4) on the post-operatory period for patients with weight regain. Conclusion: there was a predominance of females and high satisfaction with surgery. Important symptoms of mental disorders were identified and must receive attention since they may impair treatment adherence and patients’ quality of life.